The successful use of a submersible ultrasound to confirm pregnancy on free swimming bull sharks, Carcharhinus leucas, in a provisioned shark site - Hoyos-Padilla, Edgar Mauricio; Casanova-Santamaría, Irene; Loria-Correa, Jorge Carlos; Sulikowski, James (Frontiers in Marine Science, 2023)
A prototype, fully submersible, high definition ultrasound was used to determine the reproductive state of wild, free-swimming bull sharks, Carcharhinus leucas, at a provisioned shark diving site in Playa del Carmen, Mexico. During two opportunistic dives, the presence of embryos was confirmed in three female sharks (greater than 2.0 m total length) and emphasizes the importance of developing and linking emerging technologies with shark diving sites for the conservation of elasmobranch species.